Bead beating-based continuous flow cell lysis in a microfluidic device. Issue 29 (26th April 2015) - Berasaluce, A.; Matthys, L.; Mujika, J.; Antoñana-Díez, M.; Valero, A.; Agirregabiria, M.
<x xml:space="preserve">Abstract</x> This paper describes a bead beating-based miniaturized cell lysis device that works in continuous flow allowing the analysis of large volumes of samples without previous treatment.